Dentoalveolar and maxillofacial surgery - Stanko, Peter, 1954-; Poruban, Dušan, 1953-; Novotňáková, Daniela; Hollý, Dušan (Bratislava : Univerzita Komenského v Bratislave, 2012)
This monograph provides the knowledge not only for general dentists and dental specialists interested in the dentoalveolar and maxillofacial surgery, but also has a large interdisciplinary approach i. e. includes information for otorinolaryngologists, ophthalmologists, plastic surgeons, neurosurgeons and other specialists dealing with treatmentof the head and neck region.
Bibliogr. odkazy
Skratky
Keywords: chirurgia ústnej dutiny -- metódy -- vybavenie prístrojové a nástrojové; výkony chirurgické stomatologické a maxilofaciálne -- metódy -- vybavenie prístrojové a nástrojové